Gender differences in Crime Committal in Delta State, Nigeria - May Omogho, Esiri (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Within the traditional setting, the female gender is not always seen as a prime factor in criminal activities in the society. This was largely because the female gender is considered a weaker sex as compared to the male counterpart in the society. The increasing numbers of women/female prisoners in recent history particularly in Nigeria however, revealed the opposite, which therefore needs an investigation. Hence this paper aimed at an empirical investigation of the differences in the number of female and male prison inmates, and the crimes they commit in Delta State of Nigeria. For this purpose, the study adopted the expo-factor design and used a structured questionnaire to gather primary data while secondary data was collected from the state’s police headquarter. Data were analyzed using Pearson’s Product Moment Correlation, t-test, percentages and proportions. The study revealed that there were fewer women prison inmates than men; there is little or no relationship between women and reported crime; crimes committed by women are on the increase as compared to those committed by men; and gender roles does determine crime. This paper therefore recommend that governmental and non-governmental agencies/organizations should encourage and carry out indebt studies, seminars and workshops on traditional and changing gender roles and how they produce or influence criminality and the criminal justice process, with a view to reducing criminal behavior and activities.